NanoFe3O4 as Solid Electron Shuttles to Accelerate Acetotrophic Methanogenesis by Methanosarcina barkeri - Fu, Li; Zhou, Ting; Wang, Jingyuan; You, Lexing; Lu, Yahai; Yu, Linpeng; Zhou, Shungui (Frontiers in Microbiology, 2019)
Magnetite nanoparticles (nanoFe3O4) have been reported to facilitate direct interspecies electron transfer (DIET) between syntrophic bacteria and methanogens thereby improving syntrophic methanogenesis. However, whether or how nanoFe3O4 affects acetotrophic methanogenesis remain unknown. Herein, we demonstrate the unique role of nanoFe3O4 in accelerating methane production from direct acetotrophic methanogenesis in Methanosarcina-enriched cultures, which was further confirmed by pure cultures of Methanosarcina barkeri. Compared with other nanomaterials of higher electrical conductivity such as carbon nanotubes and graphite, nanoFe3O4 with mixed valence Fe(II) and Fe(III) had the most significant stimulatory effect on methane production, suggesting its redox activity rather than electrical conductivity led to enhanced methanogenesis by M. barkeri. Cell morphology and spectroscopy analysis revealed that nanoFe3O4 penetrated into the cell membrane and cytoplasm of M. barkeri. These results provide the unprecedented possibility that nanoFe3O4 in the cell membrane of methanogens serve as electron shuttles to facilitate intracellular electron transfer and thus enhance methane production. This work has important implications not only for understanding the mechanisms of mineral-methanogen interaction but also for optimizing engineered methanogenic processes.